Relationship Between Mother’s Parenting Pattern, Energy And Protein Adequacy, And Duration Of Toddler Screen Time With Nutritional Status Of Toddlers Aged 24-59 Months At Putat Jaya Community Health Center In Surabaya - Arianti, Cindy Dwi; Nur Afifah, Choirul Anna (Jurnal Gizi dan Kesehatan Nusantara, 2025)
Toddlers experience accelerated physical growth and intellectual development, so it is called the golden age. During this period, toddlers are also susceptible to nutritional problems that can be influenced by the mother’s parenting pattern, the level of energy and protein adequacy, and the duration of screen time. This study aims to determine: (1.) the relationship between the mother’s parenting pattern and the nutritional status of toddlers, (2.) the relationship between the level of energy and protein adequacy and the nutritional status of toddlers, and (3.) the relationship between the duration of toddler screen time and the nutritional status of toddlers. The type of method used is a quantitative method with a cross-sectional design. The sample consisted of 104 toddlers from 8 Posyandus taken using a purposive sampling technique. Bivariate analysis used the Spearman Rank test. The results showed that there was a relationship between parenting patterns and the nutritional status of toddlers (p = 0.006). There was a relationship between the level of energy adequacy (p = 0.000) and protein (p = 0.019) of toddlers and the nutritional status of toddlers. However, there was no relationship between the duration of screen time and the nutritional status of toddlers (p = 0.127). The conclusion of this study is that good maternal parenting patterns, adequate levels of energy and protein sufficiency, and limiting the duration of toddler screen time with sufficient physical activity can optimize the nutritional status of toddlers. This study recommends that education is needed regarding the implementation of maternal parenting patterns, meeting energy and protein needs, limiting the duration and content of toddler screen time, and physical activity in toddlers so that nutritional status becomes good.